Method for preparing high-strength regenerated cement from hardened cement powder
By adjusting the pretreatment and calcining conditions of hardened cement, combined with the gelling reaction, the compressive strength of the recycled cement is improved, the existing problem of insufficient strength of recycled cement is solved, and high-efficiency and energy-saving high-strength recycled cement is achieved.
Patent Information
- Application Number
- CN202411539842.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-03
AI Technical Summary
The unbounded compressive strength of existing recycled cement is mostly below 50MPa, and there is a problem that the strength is not high enough.
High-strength regenerated cement is prepared by pretreating and ball milling, mixing gypsum and fly ash and calcining it, adjusting the lime saturation coefficient, silicon rate and aluminum rate, and combining NaOH and Na2SiO3 solutions for gelation reaction to prepare high-strength regenerated cement.
The unlimited compressive strength of recycled cement is improved to 50~75MPa, which reduces firing temperature and carbon emissions, saves energy and natural ore resources, and improves the durability and use range of recycled cement.
Smart Images

Figure BDA0005112519440000041 
Figure BDA0005112519440000081 
Figure BDA0005112519440000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a method for preparing high-strength recycled cement from hardened cement powder. Background Art
[0002] my country has generated a large amount of construction waste due to the demolition of buildings or structures, of which waste concrete accounts for more than 60%. These waste concretes not only occupy a large amount of land space, but also pollute the environment. If the waste concrete can be recycled, it will be of great significance for the recycling of construction waste in my country. Among them, waste concrete is mainly composed of coarse aggregate (including pebbles or crushed stones), fine aggregate (sand) and hardened cement. The coarse and fine aggregates and fine aggregates mainly play the role of physical filling and skeleton, while hardened cement mainly plays the role of bonding coarse and fine aggregates. Through crushing, high-temperature heating, ball milling, screening and other processes, high-purity hardened cement powder can be obtained. The hardened cement powder mainly contains potentially active mineral components such as hydrated tricalcium silicate and hydrated dicalcium silicate. Therefore, under various activation methods, the hardened cement powder can be made into recycled cement, which can not only realize the green cycle of the cement industry, but also protect the ecological environment.
[0003] At present, some patents on the research of recycled cement have been disclosed in some prior arts, such as Chinese patent (CN112429984A), which discloses the use of waste concrete, bluestone, diatomite, refined iron powder and alumina powder to prepare recycled cement, and the unconfined compressive strength of the recycled cement is between 30 and 50 MPa after testing. Chinese patent (CN102515584B) discloses the use of waste concrete, slag, steel slag, gypsum, silicate cement clinker and water reducer to prepare recycled cement, and the unconfined compressive strength of the recycled cement is about 10 to 35 MPa after testing. Chinese patent (CN117865639A) discloses the use of cement, recycled micro powder, fly ash, hydrophobic nano silica, sodium silicate and ferrous sulfate to prepare recycled cement, but the unconfined compressive strength test result of the recycled cement is not given in its conclusion. The Chinese patent (CN113620617A) firstly mixes waste concrete powder, slag, coal gangue powder, limestone powder and clay to obtain a mixed powder, then calcines the mixed powder at 1000-1100°C for 3-5 hours, then calcines at 1200-1300°C for 0.5-1 hour, and finally cools the mixture to obtain recycled cement clinker, but similarly, the conclusion does not give the unconfined compressive strength result. The Chinese patent (CN104446042A) firstly mixes waste concrete powder, limestone powder, clay, iron powder and coal to obtain a mixed powder, then calcines the mixed powder at 800-1000°C and keeps it warm for 20-60 minutes, then calcines at 1200-1500°C and keeps it warm for 30-70 minutes, and finally grinds it to make recycled cement, but similarly, the conclusion does not give the unconfined compressive strength result of recycled cement. Chinese patent (CN104276772B) first calcines gypsum at 300-800℃, calcines waste concrete at 800-900℃, and then mixes the calcined products of gypsum and waste concrete with water-quenched slag, potassium dihydrogen phosphate, and metakaolin to obtain a mixed powder; finally, the mixed powder is ground into recycled cement, and the unconfined compressive strength of the recycled cement is between 50 and 60MPa after testing. Chinese patent (CN1834051A) discloses adding calcium oxide to primary cement to obtain a mixed powder, and then calcining it at 650℃, cooling it to obtain recycled cement, and its unconfined compressive strength is between 25 and 35MPa after testing. Chinese patent (CN101215114A) discloses first calcining waste concrete at 750-800℃, and then mixing the calcined product with cement to obtain recycled cement, and its unconfined compressive strength is between 30 and 50MPa after testing.The Chinese patent (CN113979654A) discloses that hardened cement powder is first dissolved in acetic acid solution and subjected to acid treatment to obtain a precursor powder, and then the precursor powder is mixed with an alkaline solution to obtain a gelling liquid, and finally the gelling liquid is mixed with the hardened cement powder to obtain a regenerated cement slurry. After testing, its early unconfined compressive strength is between 2 and 7 MPa.
[0004] From the above, it can be seen that among some of the existing technologies regarding recycled cement currently disclosed, the unconfined compressive strength of most recycled cement is below 50 MPa, and there is a problem of insufficient strength. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing high-strength recycled cement from hardened cement powder in view of the problem that the strength of recycled cement prepared by the prior art is not high enough. The method is mainly used for the preparation of high-strength recycled cement. The method can obtain recycled cement with an unconfined compressive strength of 50 to 75 MPa, which provides a new method for the research and development of high-strength recycled cement.
[0006] To achieve the above object, the present invention is implemented by the following technical solutions:
[0007] The present invention provides a method for preparing high-strength recycled cement from hardened cement powder, the method comprising the following steps:
[0008] S1. Pretreatment of hardened cement: crushing the hardened cement and then drying it for standby use;
[0009] S2. Preparation of recycled cement raw material: ball-milling the pretreated hardened cement to obtain hardened cement powder, and then mixing gypsum with the hardened cement powder, grinding the mixture, and sieving the mixture to obtain recycled cement raw material;
[0010] S3, preparation of recycled cement clinker: calcining the recycled cement raw material, cooling it, and then mixing and grinding it with fly ash and gypsum to obtain a mixed powder;
[0011] ① If the lime saturation coefficient (K H ) satisfies 0.8≤K H ≤1, the silicon ratio (n) satisfies 1.5≤n≤3, and the aluminum ratio (P) satisfies 1≤P≤2, then the mixed powder is sieved to obtain recycled cement clinker;
[0012] ② If the lime saturation coefficient (K H ), silicon ratio (n) and aluminum ratio (P) do not satisfy the above relationship, at least one of CaO, SO2, Al2O3, Fe2O3 is used as a supplementary material to adjust the lime saturation coefficient (K) of the mixed powder. H), silicon ratio (n) and aluminum ratio (P) so as to satisfy the above relationship, and then screen to obtain recycled cement clinker;
[0013] Wherein, the lime saturation coefficient (K H ), silicon ratio (n) and aluminum ratio (P) are calculated as follows:
[0014]
[0015] S4, preparation of precursor solution: stirring and mixing NaOH aqueous solution and Na2SiO3 aqueous solution to obtain a precursor solution;
[0016] S5. Preparation of recycled cement: stirring and mixing the recycled cement clinker, water reducing agent, retarder and the precursor solution to prepare recycled cement.
[0017] Furthermore, a method for preparing high-strength recycled cement from hardened cement powder: Step S1, pretreatment of hardened cement: crush the hardened cement into particles with a diameter of 3.0-6.0 cm, and then dry them in an oven at a temperature of 50-70° C. for 12-24 hours for use.
[0018] Furthermore, a method for preparing high-strength recycled cement from hardened cement powder: Step S2, preparation of recycled cement raw material: ball-milling the pretreated hardened cement to obtain hardened cement powder with a particle size of less than 75.0 μm; then mixing gypsum with the hardened cement powder and grinding for 10 to 15 minutes, sieving the ground powder to obtain recycled cement raw material with a particle size of less than 75.0 μm; wherein the mass fraction of gypsum in the recycled cement raw material is 5.0 to 20.0 wt%.
[0019] Furthermore, a method for preparing high-strength recycled cement from hardened cement powder: Step S3, preparation of recycled cement clinker: placing the recycled cement raw material in a combustion furnace and heating it to 1250-1350°C at a rate of 5-10°C / min for calcination, continuing to keep warm for 60-80 minutes after the heating is completed, and then mixing and grinding with fly ash and gypsum after cooling to obtain a mixed powder; wherein the mass fraction of fly ash in the mixed powder is 10.0-15.0wt%, the mass fraction of gypsum is 5.0-15.0wt%, and the remainder is the calcined recycled cement raw material.
[0020] Further, a method for preparing high-strength recycled cement from hardened cement powder: step S3, for satisfying the lime saturation coefficient (K H ), silicon rate (n) and aluminum rate (P) required by the mixed powder are sieved to obtain a powder material with a particle size less than 75.0 μm, which is the recycled cement clinker.
[0021] Furthermore, a method for preparing high-strength recycled cement from hardened cement powder: Step S4, preparation of a precursor solution: magnetically stirring and mixing a 1.0-2.0 mol / L NaOH aqueous solution and a 1.0-2.0 mol / L Na2SiO3 aqueous solution for 5-10 minutes to obtain a precursor solution; wherein the volume ratio of the NaOH aqueous solution to the Na2SiO3 aqueous solution is (1-2): (1-2).
[0022] Furthermore, a method for preparing high-strength recycled cement from hardened cement powder: Step S5, preparation of recycled cement: stirring and mixing the recycled cement clinker, water reducer, retarder and precursor solution to prepare recycled cement; wherein the amount of the water reducer is 2.0-6.0% of the mass of the recycled cement clinker, the amount of the retarder is 5.0-10.0% of the mass of the recycled cement clinker, and the amount of the precursor solution is 16.0-25.0% of the mass of the recycled cement clinker.
[0023] Furthermore, a method for preparing high-strength recycled cement from hardened cement powder: the water reducer is a polyhydroxy acid water reducer.
[0024] Furthermore, a method for preparing high-strength recycled cement from hardened cement powder: the retarder is citric acid.
[0025] Specifically, the citric acid retarder used in the present invention can improve the plasticity and fluidity of recycled cement and reduce cracking; at the same time, it can also reduce the shrinkage and cracking of recycled cement and improve its durability; citric acid can also neutralize the alkaline substances in cement and inhibit the hydration reaction of cement, thereby delaying coagulation and hardening, improving the coagulation time of recycled cement and improving working performance.
[0026] In addition, the present invention optimizes the addition amount of citric acid to further ensure the above performance, while excessive addition will have a negative impact on the performance of the recycled cement.
[0027] Beneficial effects of the present invention:
[0028] (1) The firing temperature of ordinary Portland cement is generally around 1450°C, while the firing temperature of the recycled cement of the present invention is 1250-1350°C, which reduces heat release by about 7-16% and carbon emissions by 10-15%, thus saving energy and protecting the ecological environment.
[0029] (2) The unconfined compressive strength of recycled cement prepared by the currently disclosed prior art is mostly below 50 MPa, while the unconfined compressive strength of recycled cement prepared by the method of the present invention is between 50 and 75 MPa, which obviously gets rid of the disadvantage of low strength of recycled cement prepared by the prior art, expands the application scope of recycled cement, and improves the durability of recycled cement.
[0030] (3) The raw materials for the production of ordinary Portland cement are mainly limestone, clay, coal and gypsum, while the raw materials of the present invention mainly come from waste concrete. 0.2 to 0.25 tons of hardened cement can be separated from 1 ton of waste concrete. The present invention can save an average of 0.7 to 0.8 tons of natural ore per ton of raw materials, and an average of 600 to 700 yuan per ton of raw materials. This not only saves natural ore resources, but also greatly reduces the cost of recycled cement production. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] This embodiment 1 provides a method for preparing high-strength recycled cement from hardened cement powder, using a certain original cement type of silicate cement, the original cement grade is 32.5R, and the original hardened cement strength grade is C25. The method includes the following specific steps:
[0034] S1. Pretreatment of hardened cement: crush the hardened cement (the original hardened cement strength grade is C25) into particles with a diameter of 3.0 to 6.0 cm, then put the hardened cement particles into an oven, set the oven temperature to 60° C., set the drying time to 24 hours, and dry them, and store the dried hardened cement particles in a drying oven for use;
[0035] S2, preparation of recycled cement raw material: placing the hardened cement particles pretreated in step S1 in a ball mill for ball milling to obtain hardened cement powder with a particle size of less than 75.0 μm; then mixing gypsum (Ca2SO4·0.5H2O) and the hardened cement powder in a grinding mill for grinding for 15 minutes, and sieving the ground powder to obtain recycled cement raw material with a particle size of less than 75.0 μm;
[0036] Wherein, the recycled cement raw material comprises the following components by mass fraction: 10.0wt% of gypsum and 90.0wt% of hardened cement powder;
[0037] S3, preparation of recycled cement clinker: placing the recycled cement raw material in a combustion furnace and heating it to 1350°C at a rate of 5°C / min for calcination, and then continuing to keep the temperature for 60 minutes after the heating is completed, and then mixing and grinding with fly ash and gypsum after natural cooling to obtain a mixed powder;
[0038] The mixed powder comprises the following components in mass fractions: 75.0wt% recycled cement raw material, 10.0wt% fly ash and 15.0wt% gypsum;
[0039] The lime saturation coefficient K of the mixed powder is measured. H =0.68, which does not satisfy 0.8≤K H ≤1; while the silicon content (n) and aluminum content (P) of the mixed powder satisfy the relationship of 1.5≤n≤3 and 1≤P≤2 respectively. Therefore, 10% CaO of the mixed powder is added as a supplementary material to the recycled cement raw material for re-calcination. The lime saturation coefficient (K H ), silicon ratio (n) and aluminum ratio (P) all satisfy the above relationship, and the lime saturation coefficient (K H ), silicon ratio (n) and aluminum ratio (P) are sieved to obtain a powder material with a particle size less than 75.0 μm, which is the recycled cement clinker;
[0040] Wherein, the lime saturation coefficient (K H ), silicon ratio (n) and aluminum ratio (P) are calculated as follows:
[0041]
[0042] S4. Preparation of precursor solution: first prepare a 1.2 mol / L NaOH aqueous solution, then prepare a 1.6 mol / L Na2SiO3 aqueous solution and stir them evenly on a heated magnetic stirrer, the stirring temperature is set to 50°C, and the stirring time is set to 15 minutes; finally, pour the NaOH aqueous solution into the Na2SiO3 aqueous solution at a volume ratio of 1:1 and continue to stir magnetically for 10 minutes to obtain a precursor solution;
[0043] S5. Preparation of recycled cement: 10.0 kg of recycled cement clinker was put into a mixer, and then 0.5 kg of polyhydroxy acid water reducer was added, followed by 0.8 kg of citric acid (retarder), and 1.8 kg of precursor solution was added, and the mixture was stirred and mixed to finally obtain recycled cement.
[0044] Example 2
[0045] The difference between Example 2 and Example 1 is that in Example 2, the amount of polyhydroxy acid water reducer added is 0.3 kg, the amount of citric acid retarder added is 0.5 kg, and the amount of precursor solution added is 2.1 kg; in Example 2, the concentration of NaOH aqueous solution is 1.5 mol / L, the concentration of Na2SiO3 aqueous solution is 1.1 mol / L, the volume ratio of NaOH aqueous solution to Na2SiO3 aqueous solution is 1:2, and the other conditions of Example 2 are the same as those of Example 1.
[0046] Example 3
[0047] The difference between Example 3 and Example 1 is that in Example 3, the amount of polyhydroxy acid water reducer added is 0.6 kg, the amount of citric acid retarder added is 0.9 kg, and the amount of precursor solution added is 2.5 kg; in Example 3, the concentration of NaOH aqueous solution is 1.9 mol / L, the concentration of Na2SiO3 aqueous solution is 1.8 mol / L, the volume ratio of NaOH aqueous solution to Na2SiO3 aqueous solution is 2:1, and the other conditions of Example 3 are the same as those of Example 1.
[0048] Test: The recycled cements of Examples 1 to 3 were poured into a cubic mold with a side length of 10 cm, respectively. The molds were removed after 2 days to obtain recycled cement test blocks. The recycled cement test blocks were then moved to a standard concrete curing room for curing for 28 days. Finally, the unconfined compressive strength of the recycled cement test blocks was tested. The test results are shown in Table 1:
[0049] Table 1 shows the composition and unconfined compressive strength test results of recycled cement in Examples 1 to 3
[0050]
[0051]
[0052] Example 4
[0053] This embodiment 4 provides a method for preparing high-strength recycled cement from hardened cement powder, using a certain original cement type of silicate cement, the original cement grade is 32.5R, and the original hardened cement strength grade is C35. The method includes the following specific steps:
[0054] S1. Pretreatment of hardened cement: crush the hardened cement (the original hardened cement strength grade is C35) into particles with a diameter of 3.0 to 6.0 cm, then put the hardened cement particles into an oven, set the oven temperature to 60° C., set the drying time to 24 hours, and dry them. Store the dried hardened cement particles in a drying oven for use;
[0055] S2, preparation of recycled cement raw material: placing the hardened cement particles pretreated in step S1 in a ball mill for ball milling to obtain hardened cement powder with a particle size of less than 75.0 μm; then mixing gypsum (Ca2SO4·0.5H2O) and the hardened cement powder in a grinding mill for grinding for 15 minutes, and sieving the ground powder to obtain recycled cement raw material with a particle size of less than 75.0 μm;
[0056] Wherein, the recycled cement raw material comprises the following components by mass fraction: 10.0wt% of gypsum and 90.0wt% of hardened cement powder;
[0057] S3, preparation of recycled cement clinker: placing the recycled cement raw material in a combustion furnace and heating it to 1350°C at a rate of 5°C / min for calcination, and then continuing to keep the temperature for 60 minutes after the heating is completed, and then mixing and grinding with fly ash and gypsum after natural cooling to obtain a mixed powder;
[0058] The mixed powder comprises the following components in mass fractions: 75.0wt% recycled cement raw material, 10.0wt% fly ash and 15.0wt% gypsum;
[0059] The lime saturation coefficient (K) of the mixed powder was measured. H ), silicon ratio (n) and aluminum ratio (P) satisfy 0.8≤K H ≤1, 1.5≤n≤3, 1≤P≤2, so there is no need to add supplementary materials to meet the lime saturation coefficient (K H ), silicon ratio (n) and aluminum ratio (P) are sieved to obtain a powder material with a particle size less than 75.0 μm, which is the recycled cement clinker;
[0060] S4. Preparation of precursor solution: first prepare a 1.2 mol / L NaOH aqueous solution, then prepare a 1.6 mol / L Na2SiO3 aqueous solution and stir them evenly on a heated magnetic stirrer, the stirring temperature is set to 50°C, and the stirring time is set to 15 minutes; finally, pour the NaOH aqueous solution into the Na2SiO3 aqueous solution at a volume ratio of 1:1 and continue to stir magnetically for 10 minutes to obtain a precursor solution;
[0061] S5. Preparation of recycled cement: 10.0 kg of recycled cement clinker was put into a mixer, and then 0.5 kg of polyhydroxy acid water reducer was added, followed by 0.8 kg of citric acid (retarder), and 1.8 kg of precursor solution was added, and the mixture was stirred and mixed to finally obtain recycled cement.
[0062] Example 5
[0063] The difference between Example 5 and Example 4 is that the amount of the precursor solution added in Example 5 is 2.1 kg, and the other conditions are the same as those in Example 4.
[0064] Example 6
[0065] The difference between Example 6 and Example 4 is that the amount of precursor solution added in Example 6 is 2.5 kg, and the other conditions are the same as those in Example 4.
[0066] Test: The recycled cements of Examples 4 to 6 were poured into a cubic mold with a side length of 10 cm, and the molds were removed after 2 days to obtain recycled cement test blocks. The recycled cement test blocks were then moved to a standard concrete curing room for curing for 28 days. Finally, the unconfined compressive strength of the recycled cement test blocks was tested. The test results are shown in Table 2:
[0067] Table 2 shows the composition and unconfined compressive strength test results of recycled cement in Examples 4 to 6
[0068] Recycled cement clinker Water reducing agent Retarder Precursor solution Unconfined compressive strength Example 4 10.0kg 0.5kg 0.8kg 1.8kg 63.9MPa Example 5 10.0kg 0.5kg 0.8kg 2.1kg 57.3MPa Example 6 10.0kg 0.5kg 0.8kg 2.5kg 54.5MPa
[0069] Example 7
[0070] This embodiment 7 provides a method for preparing high-strength recycled cement from hardened cement powder, using a certain original cement type of silicate cement, the original cement grade is 42.5R, and the original hardened cement strength grade is C40. The method includes the following specific steps:
[0071] S1. Pretreatment of hardened cement: crush the hardened cement (the original hardened cement strength grade is C40) into particles with a diameter of 3.0 to 6.0 cm, then put the hardened cement particles into an oven, set the oven temperature to 60° C., set the drying time to 24 hours, and dry them, and store the dried hardened cement particles in a drying oven for use;
[0072] S2, preparation of recycled cement raw material: placing the hardened cement particles pretreated in step S1 in a ball mill for ball milling to obtain hardened cement powder with a particle size of less than 75.0 μm; then mixing gypsum (Ca2SO4·0.5H2O) and the hardened cement powder in a grinding mill for grinding for 15 minutes, and sieving the ground powder to obtain recycled cement raw material with a particle size of less than 75.0 μm;
[0073] Wherein, the recycled cement raw material comprises the following components by mass fraction: 10.0wt% of gypsum and 90.0wt% of hardened cement powder;
[0074] S3, preparation of recycled cement clinker: placing the recycled cement raw material in a combustion furnace and heating it to 1350°C at a rate of 5°C / min for calcination, and then continuing to keep the temperature for 60 minutes after the heating is completed, and then mixing and grinding with fly ash and gypsum after natural cooling to obtain a mixed powder;
[0075] The mixed powder comprises the following components in mass fractions: 75.0wt% recycled cement raw material, 10.0wt% fly ash and 15.0wt% gypsum;
[0076] The lime saturation coefficient (K) of the mixed powder was measured. H ), silicon ratio (n) and aluminum ratio (P) satisfy 0.8≤K H ≤1, 1.5≤n≤3, 1≤P≤2, so there is no need to add supplementary materials to meet the lime saturation coefficient (K H ), silicon ratio (n) and aluminum ratio (P) are sieved to obtain a powder material with a particle size less than 75.0 μm, which is the recycled cement clinker;
[0077] S4. Preparation of precursor solution: first prepare a 1.2 mol / L NaOH aqueous solution, then prepare a 1.6 mol / L Na2SiO3 aqueous solution and stir them evenly on a heated magnetic stirrer, the stirring temperature is set to 50°C, and the stirring time is set to 15 minutes; finally, pour the NaOH aqueous solution into the Na2SiO3 aqueous solution at a volume ratio of 1:1 and continue to stir magnetically for 10 minutes to obtain a precursor solution;
[0078] S5. Preparation of recycled cement: 10.0 kg of recycled cement clinker was put into a mixer, and then 0.5 kg of polyhydroxy acid water reducer was added, followed by 0.8 kg of citric acid (retarder), and 1.6 kg of precursor solution was added, and the mixture was stirred and mixed to finally obtain recycled cement.
[0079] Example 8
[0080] The difference between Example 8 and Example 7 is that the amount of the precursor solution added in Example 8 is 1.9 kg, and the other conditions are the same as those in Example 7.
[0081] Example 9
[0082] The difference between Example 9 and Example 7 is that the amount of the precursor solution added in Example 9 is 2.2 kg, and the other conditions are the same as those in Example 7.
[0083] Test: The recycled cements of Examples 7 to 9 were poured into a cubic mold with a side length of 10 cm, respectively. The molds were removed after 2 days to obtain recycled cement test blocks. The recycled cement test blocks were then moved to a standard concrete curing room for curing for 28 days. Finally, the unconfined compressive strength of the recycled cement test blocks was tested. The test results are shown in Table 3:
[0084] Table 3 shows the composition and unconfined compressive strength test results of recycled cement in Examples 7 to 9
[0085] Recycled cement clinker Water reducing agent Retarder Precursor solution Unconfined compressive strength Example 7 10.0kg 0.5kg 0.8kg 1.6kg 67.8MPa Example 8 10.0kg 0.5kg 0.8kg 1.9kg 63.7MPa Example 9 10.0kg 0.5kg 0.8kg 2.2kg 58.2MPa
[0086] Example 10
[0087] This embodiment 10 provides a method for preparing high-strength recycled cement from hardened cement powder, using a certain original cement type of silicate cement, the original cement grade is 42.5R, and the original hardened cement strength grade is C50. The method includes the following specific steps:
[0088] S1. Pretreatment of hardened cement: crush the hardened cement (the original hardened cement strength grade is C40) into particles with a diameter of 3.0 to 6.0 cm, then put the hardened cement particles into an oven, set the oven temperature to 60° C., set the drying time to 24 hours, and dry them, and store the dried hardened cement particles in a drying oven for use;
[0089] S2, preparation of recycled cement raw material: placing the hardened cement particles pretreated in step S1 in a ball mill for ball milling to obtain hardened cement powder with a particle size of less than 75.0 μm; then mixing gypsum (Ca2SO4·0.5H2O) and the hardened cement powder in a grinding mill for grinding for 15 minutes, and sieving the ground powder to obtain recycled cement raw material with a particle size of less than 75.0 μm;
[0090] Wherein, the recycled cement raw material comprises the following components by mass fraction: 10.0wt% of gypsum and 90.0wt% of hardened cement powder;
[0091] S3, preparation of recycled cement clinker: placing the recycled cement raw material in a combustion furnace and heating it to 1250°C at a rate of 10°C / min for calcination, and then continuing to keep the temperature for 70 minutes after the heating is completed, and then mixing and grinding with fly ash and gypsum after natural cooling to obtain a mixed powder;
[0092] The mixed powder comprises the following components in mass fractions: 75.0wt% recycled cement raw material, 10.0wt% fly ash and 15.0wt% gypsum;
[0093] The lime saturation coefficient (K) of the mixed powder was measured. H), silicon ratio (n) and aluminum ratio (P) satisfy 0.8≤K H ≤1, 1.5≤n≤3, 1≤P≤2, so there is no need to add supplementary materials to meet the lime saturation coefficient (K H ), silicon ratio (n) and aluminum ratio (P) are sieved to obtain a powder material with a particle size less than 75.0 μm, which is the recycled cement clinker;
[0094] S4. Preparation of precursor solution: first prepare a 1.2 mol / L NaOH aqueous solution, then prepare a 1.6 mol / L Na2SiO3 aqueous solution and stir them evenly on a heated magnetic stirrer, the stirring temperature is set to 50°C, and the stirring time is set to 15 minutes; finally, pour the NaOH aqueous solution into the Na2SiO3 aqueous solution at a volume ratio of 1:1 and continue to stir magnetically for 10 minutes to obtain a precursor solution;
[0095] S5. Preparation of recycled cement: 10.0 kg of recycled cement clinker was put into a mixer, and then 0.5 kg of polyhydroxy acid water reducer was added, followed by 0.8 kg of citric acid (retarder), and 1.6 kg of precursor solution was added, and the mixture was stirred and mixed to finally obtain recycled cement.
[0096] Embodiment 11
[0097] The difference between Example 11 and Example 10 is that the amount of precursor solution added in Example 11 is 1.9 kg, and the other conditions are the same as those in Example 10.
[0098] Example 12
[0099] The difference between Example 12 and Example 10 is that the amount of precursor solution added in Example 12 is 2.2 kg, and the other conditions are the same as those in Example 10.
[0100] Test: The recycled cements of Examples 10 to 12 were respectively poured into a cubic mold with a side length of 10 cm, and the molds were removed after 2 days to obtain recycled cement test blocks. The recycled cement test blocks were then moved to a standard concrete curing room for curing for 28 days, and finally the unconfined compressive strength of the recycled cement test blocks was tested. The test results are shown in Table 4:
[0101] Table 4 shows the composition and unconfined compressive strength test results of recycled cement in Examples 10 to 12
[0102] Recycled cement clinker Water reducing agent Retarder Precursor solution Unconfined compressive strength Example 10 10.0kg 0.5kg 0.8kg 1.6kg 71.4MPa Embodiment 11 10.0kg 0.5kg 0.8kg 1.9kg 68.3MPa Example 12 10.0kg 0.5kg 0.8kg 2.2kg 64.1MPa
[0103] In summary, it can be seen that the method of the present invention can be used for the preparation of high-strength recycled cement, and it can produce recycled cement with an unconfined compressive strength of 50 to 75 MPa, which obviously gets rid of the disadvantage of low strength (less than 50 MPa) of recycled cement prepared by the prior art, expands the scope of use of recycled cement, and improves the durability of recycled cement. The method of the present invention provides a new method for the research and development of high-strength recycled cement.
[0104] The above are preferred embodiments of the present invention and are only used to explain the present invention, not to limit the present invention. Any obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing high-strength recycled cement from hardened cement powder, characterized in that: The method comprises the following steps: S1. Pretreatment of hardened cement: crushing the hardened cement and then drying it for standby use; S2. Preparation of recycled cement raw material: ball-milling the pretreated hardened cement to obtain hardened cement powder, and then mixing gypsum with the hardened cement powder, grinding the mixture, and sieving the mixture to obtain recycled cement raw material; S3, preparation of recycled cement clinker: calcining the recycled cement raw material, cooling it, and then mixing and grinding it with fly ash and gypsum to obtain a mixed powder; ① If the lime saturation coefficient (K H ) satisfies 0.8≤K H ≤1, the silicon ratio (n) satisfies 1.5≤n≤3, and the aluminum ratio (P) satisfies 1≤P≤2, then the mixed powder is sieved to obtain recycled cement clinker; ② If the lime saturation coefficient (K H ), silicon ratio (n) and aluminum ratio (P) do not satisfy the above relationship, at least one of CaO, SO2, Al2O3, Fe2O3 is used as a supplementary material to adjust the lime saturation coefficient (K) of the mixed powder. H ), silicon ratio (n) and aluminum ratio (P) so as to satisfy the above relationship, and then screen to obtain recycled cement clinker; Wherein, the lime saturation coefficient (K H ), silicon ratio (n) and aluminum ratio (P) are calculated as follows: S4, preparation of precursor solution: stirring and mixing NaOH aqueous solution and Na2SiO3 aqueous solution to obtain a precursor solution; S5. Preparation of recycled cement: stirring and mixing the recycled cement clinker, water reducing agent, retarder and the precursor solution to prepare recycled cement.
2. A method for preparing high-strength recycled cement from hardened cement powder according to claim 1, characterized in that: Step S1, pretreatment of hardened cement: crush the hardened cement into particles with a diameter of 3.0-6.0 cm, and then dry them in an oven at a temperature of 50-70° C. for 12-24 hours for standby use.
3. The method for preparing high-strength recycled cement from hardened cement powder according to claim 1, characterized in that: Step S2, preparation of recycled cement raw material: ball-milling the pretreated hardened cement to obtain hardened cement powder with a particle size of less than 75.0 μm; Then, the gypsum is mixed with the hardened cement powder and ground for 10 to 15 minutes, and the ground powder is sieved to obtain recycled cement raw material with a particle size of less than 75.0 μm; wherein the mass fraction of gypsum in the recycled cement raw material is 5.0 to 20.0 wt%.
4. The method for preparing high-strength recycled cement from hardened cement powder according to claim 1, characterized in that: Step S3, preparation of recycled cement clinker: placing the recycled cement raw material in a combustion furnace and heating it to 1250-1350° C. at a rate of 5-10° C. / min for calcination, and then continuing to keep the temperature for 60-80 minutes after the heating is completed, and then mixing and grinding with fly ash and gypsum after cooling to obtain a mixed powder; The mass fraction of fly ash in the mixed powder is 10.0-15.0wt%, the mass fraction of gypsum is 5.0-15.0wt%, and the remainder is calcined recycled cement raw material.
5. The method for preparing high-strength recycled cement from hardened cement powder according to claim 1, characterized in that: Step S3: satisfy the lime saturation coefficient (K H ), silicon rate (n) and aluminum rate (P) required by the mixed powder are sieved to obtain powder material with a particle size less than 75.0μm, which is the recycled cement clinker.
6. The method for preparing high-strength recycled cement from hardened cement powder according to claim 1, characterized in that: Step S4, preparation of a precursor solution: mixing a 1.0-2.0 mol / L NaOH aqueous solution and a 1.0-2.0 mol / L Na2SiO3 aqueous solution with magnetic stirring for 5-10 minutes to obtain a precursor solution; Wherein, the volume ratio of the NaOH aqueous solution to the Na2SiO3 aqueous solution is (1-2): (1-2).
7. The method for preparing high-strength recycled cement from hardened cement powder according to claim 1, characterized in that: Step S5, preparation of recycled cement: stirring and mixing the recycled cement clinker, water reducing agent, retarder and precursor solution to prepare recycled cement; The amount of the water reducer is 2.0-6.0% of the mass of the recycled cement clinker, the amount of the retarder is 5.0-10.0% of the mass of the recycled cement clinker, and the amount of the precursor solution is 16.0-25.0% of the mass of the recycled cement clinker.
8. A method for preparing high-strength recycled cement from hardened cement powder according to claim 1 or 7, characterized in that: The water reducing agent is a polyhydroxy acid water reducing agent.
9. A method for preparing high-strength recycled cement from hardened cement powder according to claim 1 or 7, characterized in that: The retarder is citric acid.
